2011
DOI: 10.1002/da.20863
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of the effects of cognitive behavioral therapy for panic disorder on gastrointestinal distress in patients with comorbid panic disorder and irritable bowel syndrome

Abstract: Although additional research still is needed, these preliminary findings suggest that CBT for PD/A can be used to simultaneously treat comorbid symptoms of PD/A and IBS. Implications for the neurobiological models for these comorbid conditions were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The results showed that the CBSM effectively reduced negative moods (depression and anxiety) in IBS patients. This finding is consistent with Kennedy et al (32) and Gros et al (33). To adjust to their conditions, patients experience changes in daily activities, somatic reactions such as sleep disturbance, and thinking or emotions.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that the CBSM effectively reduced negative moods (depression and anxiety) in IBS patients. This finding is consistent with Kennedy et al (32) and Gros et al (33). To adjust to their conditions, patients experience changes in daily activities, somatic reactions such as sleep disturbance, and thinking or emotions.…”
Section: Discussionsupporting
confidence: 91%
“…High comorbidity between IBS and PD has been identified in the literature [3, 17, 38]. The prevalence of IBS symptoms characteristics in patients with PD varies between 25 to 44%, several symptoms being characteristic of the two disorders (nausea, diarrhea, abdominal discomfort) [3942].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the contents of intervention were self-monitoring and group work activities focused on lifestyle. Some studies [32][33][34][35] investigated the effects of self-monitoring focused on the emotions and feelings of the subjects, but we intervened in the lifestyles of the subjects using the self-monitoring method because we revealed a relationship between disordered lifestyles and IBS in our previous studies [6,7]. This study was the first to investigate the effects of lifestyle self-monitoring on the symptoms of IBS.…”
Section: Discussionmentioning
confidence: 97%